Teacher Difficulties in Learning Mathematics Class V Elementary School - Husna, Naimatul; Safrizal, Safrizal; Husnani, Husnani (Universitas Sang Bumi Ruwa Jurai, 2024)
This study was motivated by teacher difficulty teaching mathematics in elementary schools. Therefore, the purpose of this study is to identify the obstacles that elementary school teachers experience when teaching mathematics. This study uses a qualitative approach, with case study research selected utilizing a purposive sample technique. The research subject was a fifth-grade teacher at SD Negeri 20 Paninjauan. The researcher serves as the research tool. In this study, data was collected through interviews and documentation. The data and information collected are then examined using the Miles and Huberman model. The findings of this study indicate that teachers face a number of challenges when teaching mathematics, including 1) students' limited ability to grasp basic mathematical concepts; 2) low student interest in learning mathematics; 3) low mastery of mathematical formulas; and 4) student anxiety about mathematics learning.